Organisational change in hospitals: a qualitative case-study of staff perspectives - Chiara Pomare; Kate Churruca; Janet C. Long; Louise A. Ellis; Jeffrey Braithwaite (BMC, 2019)
Abstract Background Organisational change in health systems is common. Success is often tied to the actors involved, including their awareness of the change, personal engagement and ownership of it. In many health systems, one of the most common changes we are witnessing is the redevelopment of long-standing hospitals. However, we know little about how hospital staff understand and experience such potentially far-reaching organisational change. The purpose of this study is to explore the understanding and experiences of hospital staff in the early stages of organisational change, using a hospital redevelopment in Sydney, Australia as a case study. Methods Semi-structured interviews were conducted with 46 clinical and non-clinical staff working at a large metropolitan hospital. Hospital staff were moving into a new building, not moving, or had moved into a different building two years prior. Questions asked staff about their level of awareness of the upcoming redevelopment and their experiences in the early stage of this change. Qualitative data were analysed using thematic analysis. Results Some staff expressed apprehension and held negative expectations regarding the organisational change. Concerns included inadequate staffing and potential for collaboration breakdown due to new layout of workspaces. These fears were compounded by current experiences of feeling uninformed about the change, as well as feelings of being fatigued and under-staffed in the constantly changing hospital environment. Nevertheless, balancing this, many staff reported positive expectations regarding the benefits to patients of the change and the potential for staff to adapt in the face of this change. Conclusions The results of this study suggest that it is important to understand prospectively how actors involved make sense of organisational change, in order to potentially assuage concerns and alleviate negative expectations. Throughout the processes of organisational change, such as a hospital redevelopment, staff need to be engaged, adequately informed, trained, and to feel supported by management. The use of champions of varying professions and lead departments, may be useful to address concerns, adequately inform, and promote a sense of engagement among staff.